2016
DOI: 10.1177/1077699016629371
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Active Hot-Issue Communicators and Subgroup Identifiers

Abstract: This study used the situational theory of problem solving (STOPS) to investigate communication behaviors of publics formed around an intensively publicized policy issue. Results of surveying 748 participants online support the utility of STOPS to segment the hot-issue public with active communication from the general population in a Chinese context. However, problem recognition does not significantly correlate with situational motivation. Between the examined cross-situational variables, party identity serves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…This study establishes that extraneous triggering can alter an individual's assessment of a problem (Aldoory & Grunig, 2012;Chen et al, 2016;Kim et al, 2012). For example, some individuals become engaged quickly as a result of exposure to media coverage, particularly if the event/problem/coverage involves scandals or national problems (Aldoory & Van Dyke, 2006;Grunig, 1997).…”
Section: Situational Motivation In Problem Solving In Response To Insmentioning
confidence: 63%
“…This study establishes that extraneous triggering can alter an individual's assessment of a problem (Aldoory & Grunig, 2012;Chen et al, 2016;Kim et al, 2012). For example, some individuals become engaged quickly as a result of exposure to media coverage, particularly if the event/problem/coverage involves scandals or national problems (Aldoory & Van Dyke, 2006;Grunig, 1997).…”
Section: Situational Motivation In Problem Solving In Response To Insmentioning
confidence: 63%
“…Public trust in government–public relationship also reflects individuals' overall evaluation of the performance of political authorities and institutions (Miller & Listhaug, ). Accordingly, trust in this study is a concept that influences the relationship between the citizenry and the political objects in general (e.g., Chen, Hung‐Baesecke, & Kim, ; Huang, ). Based on this rationale, this study evaluates individuals' trust in their government by adapting Hon and Grunig's (, p. 19) dimensions among six levels: integrity items (the belief that government performs fairly), dependability (the belief that government will deliver its promises), and competence (the belief that the government has the ability to manage controversies or problems affecting society).…”
Section: Methodsmentioning
confidence: 99%
“…Also, going with the assumption that foreign media's coverage of air pollution in China has been mainly negative (Kay et al, 2015), it is arguable that the Chinese public that is closer to foreign media could have been more active. In earlier studies, publics' psychological activeness was found to be influenced in different ways by crosssituational traits (Chen et al, 2017;Kim et al, 2012), some by cutting short constraint recognition, and some by increasing problem recognition. Given the distinct activation routes showed in earlier studies, the current study proposes its first three hypotheses and first three mediation path models (Figure 1 H3.…”
Section: Foreign Media Affinity and Dependency As Cross-situational Amentioning
confidence: 97%
“…The current literature on hot-issue publics’ behaviour has shown empirical evidence only about the relationship between individual traits and psychological, problem-solving activeness among publics. For example, Chen et al (2017) studied how government trust influenced psychological antecedents, and found that Koreans’ trust in their government would reduce their problem recognition about the import of US beef, while giving rise to constraint recognition and referent criterion. In other words, government trust was a suppressor of psychological activeness for problem solving against the import of US beef.…”
Section: Literature Reviewmentioning
confidence: 99%